Measurement of the 87Rb[5P3/2(F′=3)−5S1/2(F=2)] Effective Nonradiative Relaxation Rate near a Metallic Film. (19th July 2010) - Liu, Jing; Shen, Yifan; Dai, Kang
Abstract : We have studied the effective nonradiative relaxation rate of the hyperfine level 87 Rb [ 5 P 3 / 2 ( F ′ = 3 ) ] near a metallic film with diode laser-induced retrofluorescence spectroscopy and saturated-absorption spectroscopy technique. The glass-vapor interface is considered as two distinct regions, a wavelength-thickness vapor layer joined to the surface and a more remote vapor region. The total experimental retrofluorescence signalS o b ( ν L ) is the summation of the signal originating from the far-field regionS T ( ν L ) and the signal originating from the near-field regions n ( ν L ) . Considering the thermalization of 87 Rb ( 5 P 3 / 2 ) atoms in the far-field region, we can approximateS T ( ν L ) by using the vertical fluorescence signal near the entrance window. Thus we get the experimental hyperfine signal profile of 87 Rb in the near-field region. The value of the effective nonradiative transfer rateA F ′ = 3 → F = 2 n f = 2.3 × 10 8 s − 1 near the metallic film is relatively large compared to the spontaneous emission rateA F ′ = 3 → F = 2 = 1.1 × 10 7 s − 1